International Migration, Income Taxes and Transfers: A Welfare Analysis - Michael S. Michael (Center for Economic Studies and ifo Institute (CESifo), 2002)
An important issue in public policy debates is the effect of international migration on welfare in source and host countries. We address this issue by constructing a general equilibrium model of a two-class source or host country. Each country produces many traded and non-traded goods, uses income taxes and distributes the tax receipts equally to all individuals. The analysis examines the effects of permanent migration on class, and national welfare. We show, among other things, that marginal immigration hurts people already in the country regardless of whether or not non-traded goods exist. The presence of international capital mobility, however, may reverse the above result.
Keywords: F22; 330; international migration; taxes; transfers; welfare